Health Literacy and Patient Activation in the Pediatric to Adult Transition in Systemic Lupus Erythematosus: Patient and Health Care Team Perspectives. Issue 9 (18th June 2022) - Ciosek, Ashley L.; Makris, Una E.; Kramer, Justin; Bermas, Bonnie L.; Solow, E. Blair; Wright, Tracey; Bitencourt, Nicole
Abstract : Objective: To identify perceived health literacy (HL) and patient activation (PA) needs during the transition from pediatric to adult rheumatology among patients with childhood‐onset systemic lupus erythematosus (cSLE). Methods: Semistructured interviews of patients and health care professionals were conducted from November 2019 through May 2020, until thematic saturation was achieved. Interviews were audio‐recorded, transcribed, coded, and analyzed using thematic analysis. Results: Thirteen post‐transition adult female participants with cSLE were recruited from a public safety‐net hospital system or from private practice. Thirteen health care team members were recruited from two pediatric and four adult rheumatology clinical sites serving patients in the same metropolitan area. Patients and health care team members acknowledged numerous HL components as important to transition, including language fluency, education, SLE‐specific knowledge, self‐efficacy, and accurate knowledge of personal medical history. Our interviews found PA to be an important component of the transition process, driven by internalization of the implications of cSLE diagnosis, self‐education, autonomy, introspection, and trustworthy doctor–patient relationships. Patients valued access to their online electronic medical record, recommended multimodal SLE‐specific education materials, and desired increased access to social workers. Health care team members stressed the importance of early preparation for transition and use of mobile medical applications and endorsed interventions such as lupus camp and increased partnership with psychologists and social workers. Conclusion: HL and PA are perceived by patients and health care team members as substantially influencing transition success. Further research is needed to evaluate whether interventions to improve HL and PA positively influence cSLE transition outcomes.